Peran Administrasi Kurikulum dalam Mengoptimalkan Pembelajaran Berbasis Artificial Intelligence (AI) - Rivaldi Rivaldi; Rahma Muthia Febriliana; Ahmad Sabri; Rully Hidayatullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Curriculum administration is all business processes that have been planned and attempted deliberately and earnestly as well as continuous guidance on teaching and learning activities effectively and efficiently in order to achieve the educational goals that have been set. The importance of curriculum administration in educational institutions, which includes the selection of materials, teaching methods, and assessments that are in accordance with educational goals and student needs. Curriculum administration plays a role in ensuring that the curriculum is well structured and organized through various levels of planning, implementation, and supervision. Curriculum evaluation is also an important part of education management, aiming to collect information about the effectiveness of curriculum implementation and the impact of learning outcomes. In addition, this journal highlights the role of teachers in curriculum administration as implementers, adapters, developers, and researchers. The presence of artificial intelligence (AI) technology presents an opportunity for educators to carry out a learning process that focuses on the needs, interests, and learning styles of students, because the independent curriculum requires educators to carry out differentiated learning as an initiative in facilitating students, especially in Pancasila education, which incidentally is still carried out by conventional models or methods.